Profesionalitas Guru dalam Proses Kegiatan Belajar Mengajar: Teacher Professionalism in the Teaching and Learning Process - Debrianti, Auliah; Ismail Abdussabir, Ahmad; Rosdiana (CV. Kalimasada Group, 2024)
The purpose of this research is to understand the perspectives of education and the responsibilities of professional teachers, which are the focus of this study. This research utilizes library exploration as its approach. The research findings indicate that professional teachers generally have responsibilities to plan learning, conduct quality learning processes, assess and evaluate learning outcomes, enhance and develop academic qualifications and competencies continuously in line with the development of science, technology, and the arts. They should act objectively and non-discriminatively based on considerations of gender, religion, ethnicity, race, and specific physical conditions, or family backgrounds, and socio-economic status of learners in the learning process. They should uphold laws, regulations, and the ethical codes of teachers, as well as religious values and ethics, while fostering national unity and unity.